Financial intermediation costs in low-income countries : the role of regulatory, institutional, and macroeconomic factors - Poghosyan, Tigran (IMF working paper, 2012)
We analyze factors driving persistently higher financial intermediation costs in low-income countries (LICs) relative to emerging market (EMs) country comparators. Using the net interest margin as a proxy for financial intermediation costs at the bank level, we find that within LICs a substantial part of the variation in interest margins can be explained by bank-specific factors: margins tend to increase with higher riskiness of credit portfolio, lower bank capitalization, and smaller bank size. Overall, we find that concentrated market structures and lack of competition in LICs banking systems and institutional weaknesses constitute the key impediments preventing financial intermediation costs from declining. Our results provide strong evidence that policies aimed at fostering banking competition and strengthening institutional frameworks can reduce intermediation costs in LICs.